Paederia Foetida L. Grows in the Western Province of Sri Lanka: a preliminary study of Physico-chemical, Phytochemical and HPTLC profiles - Hapuarachchi, S.D.; Silva, P. D. S. A.; Kodithuwakku, N.D.; Perera, P.K. (Faculty of Indigenous Medicine, University of Colombo, 2021)
Paederia foetida (Prasarini) under the family Rubiaceae is a herb used in Ayurveda preparations with hepatoprotective, anthelmintic, antibacterial, hypoglycaemic, anti-inflammatory, antioxidant, antitussive, anti-ulcer, antinociceptive, diuretic, laxative and thermogenic properties. Hence, standardization parameters are required in the quality control of herbal raw materials used in Ayurveda manufacturing.Study was aimed at developing standardization parameters for different extracts of whole aerial parts of P. foetida grown in Western Province, Sri Lanka. Matured whole aerial parts were collected from Western Province, air dried, oven dried at 45 ⁰C and powdered. Extracts were obtained from cold maceration with methanol, acetone and hot water extraction under WHO Guidelines. Each was subjected to preliminary phytochemical screening, physico-chemical tests and High Performance Thin Layer Chromatography (HPTLC). Phytochemical screening showed tannins in all extracts while carbohydrates, reducing sugars, saponins and diterpenes were found in methanol and aqueous extracts. Phenols were detected only in aqueous extract while flavonoids were found only in acetone extract. Physico-chemical parameters; total ash, acid insoluble ash, water soluble ash, loss on drying, extractability in methanol, acetone and water were 15.9±1.3% w/w, 7.7±0.8% w/w, 9.3±0.2% w/w, 14.3±0.1% w/w, 22.6±2.9% w/w, 3.6±0.1% w/w and 23.4±1.0% w/w respectively. HPTLC fingerprint of methanol extract showed 9 peaks (Rf; 0.06, 0.10, 0.12, 0.15, 0.24, 0.32, 0.57, 0.62, 0.73) with the solvent system; ethyl acetate: n-hexane: dichloromethane in 1:4:1 proportion while acetone extract also showed 9 peaks (Rf; 0.06, 0.10, 0.14, 0.16, 0.29, 0.59, 0.62, 0.66, 0.78) for the same solvent system. Reverse phase HPTLC was run for aqueous extract which showed 16 peaks (Rf; 0.07, 0.12, 0.21, 0.22, 0.27, 0.29, 0.33, 0.35, 0.44, 0.50, 0.56, 0.61, 0.63, 0.66, 0.76, 0.84) with methanol: distilled water (4:6).Hence the above criteria can be used as quality control parameters of P. foetida whole aerial parts as a raw material in Ayurveda preparations.
Keywords: HPTLC; Paederia foetida L.; phytochemical screening; quality control; standardization